IMPROVING STUDENTS’ SPEAKING ACHIEVEMENT BY DESCRIBING REALIA AT EIGHT GRADE OF MTSN PARE - Choliyuddini, Nur (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Getting the problems to convey the English orally of the foreign learners’ in the classroom, the researcher experienced to do the research if describing realia is able to improve students’ speaking achievement of the Eight Grade students of MTsN Pare.  The research conducted Classroom Action Research (CAR) as the design. It was done in B class. There were 31 students which contained 11 male students and 20 female students. The result of students speaking achievement was known by doing the observation checklist and the speaking test. However, the interview and the questionnaire were as the additional data to measure the result of students’ speaking achievement. The result of the data was to count the average and percentage of the speaking achievement. The result of the research mentioned the improvement in every cycle. The average and the percentage shown the students’ speaking achievement in cycle I was in 78,4 and 64,5%. The result of cycle 2 shown the improvement in average and the percentage in 88 and 90,1% students achieve the standard of success. The conclusion was that describing realia is the media which could improve students’ speaking achievement.